Sharing economy and sustainable supply chain perspective the role of environmental, economic and social pillar of supply chain in customer intention and sustainable development - Sumian Peng (Journal of Innovation & Knowledge (JIK), 2023)
Sustainable development is a global requirement, due to extensive economic and environmental issues, which requires research emphasis. Thus, the purpose of this study is to investigate the effect of sustainable supply chain management (SSCM) practices of sharing economy platforms on sustainable development goals (SDGs). This study addresses SSCM in terms of three pillars, the environmental pillar, economic pillar, and social pillar. The target respondents of the study are customers having relevant knowledge and sharing economy experience from China. Six hundred and fifty respondents are selected via Amazon Mechanical Turk, and questionnaires are distributed electronically. Only Chinese customers are selected for the survey. Two hundred and sixty questionnaires are used in the data analysis, which is done using the statistical tool AMOS. The results report a significant relationship between SSCM practices of sharing economy platforms and SDGs. According to the results, the three pillars of SSCM, are of key importance for SDGs. These pillars have a positive effect on promoting customer intention, which further promotes SDGs. The findings of the study are helpful for various organizations hoping to achieve SDGs in China through SSCM practices of sharing economy platforms.
Keywords: F41; Q01; P48; 650; Customer intention; Economic pillar; Environmental pillar; Sharing economy; Social pillar; Supply chain; Sustainable development goals